2015
DOI: 10.1590/0104-6632.20150321s00003211
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Malachite Ore in Ammonium Sulfate Solutions and Production of Copper Oxide

Abstract: -Malachite ore is one of the most important of oxidized copper ores. Copper production can be performed by using this ore. In this work, the leaching kinetics of malachite in ammonium sulfate solutions was investigated, and metallic copper was recovered by a cementation method from the resulting actual leach solution. Copper (II) oxide was prepared by an isothermal oxidation method from the cement copper. In the leaching experiments, the effects of reaction temperature, particle size, and stirring speed on cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 42 publications
1
9
0
2
Order By: Relevance
“…The ammoniacal system shrinking core model is the most used mathematical model for ammonical leaching kinetics [18][19][20], but it cannot explain the leaching progress in this work. Figures 2, 3, 5 and 6…”
Section: Kinetic Discussionmentioning
confidence: 99%
“…The ammoniacal system shrinking core model is the most used mathematical model for ammonical leaching kinetics [18][19][20], but it cannot explain the leaching progress in this work. Figures 2, 3, 5 and 6…”
Section: Kinetic Discussionmentioning
confidence: 99%
“…Generally, this model expressed by below described equations [11,19,31]. This model assumes that the reaction between solid and liquid reactants occurs on the outer surface of the solid particle and the reacting particles are spherical, and their size does not change during reaction [23].…”
Section: Identification Of the Leaching Mechanismmentioning
confidence: 99%
“…Researches on leaching behavior and kinetics of copper oxide ores have been extensively conducted by different lixiviants including mineral acids such as HCl, H 2 SO 4 and HNO 3 [7,[9][10][11]; organic acids such as citric acid and lactic acid [11][12][13]; chlorine [14], ammonium hydroxide or ammonium salts including ammonium chloride, ammonium sulfate, ammonium nitrate, ammonium citrate and ammonium acetate, etc. (2,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and alkaline glycine solutions [25].…”
mentioning
confidence: 99%
“…In recent times, beneficiation of ilmenite into synthetic rutile has drawn the attention of many researchers considering the increasing scarcity of natural rutile. Reference [1] reported that metal production from any metal source, like ore, concentrate, and secondary sources (various industrial wastes containing metals and scrap metals, etc.) is performed by one of the pyrometallurgical and hydrometallurgical methods, or by a combination of them.…”
Section: Introductionmentioning
confidence: 99%
“…In the leaching step in hydrometallurgy, the metal is leached using a suitable lixiviant [1]. The most efficient leaching agents are acids, due to their ability to leach both base and precious metals [4].…”
Section: Introductionmentioning
confidence: 99%